A qualitative research on emigration and identity in İzmir–Eşrefpaşa - Elif Yıldızer Özkan; Hayat Zengin Çelik (International Migration, 2021)
Eşrefpaşa has been considered as a migration settlement where every emigrant, immigrant or refugee has an opportunity to live freely according to their tradition and culture without any pressure considering the ethnic and social diversity. This article aims to comprehend how the next generations of emigrants in Eşrefpaşa describe their ancestors, identities, cultures and urban environment and highlight the transformations they faced spatially and socially. After conducting an in-depth interview study of 26 people between the ages of 35 and 85~years, the analysis revealed that second and third generations preserve their culture, while the identity of emigration has substantially decreased for the fourth generation due to the undeniable effects of individualism and globalization on society since the early 2000s. The outcomes obtained in this paper, the most up-to-date of the rare oral interviews performed with the emigrants in Eşrefpaşa, can be used as a resource of discussion for developing future research.
Keywords: 300